2011
DOI: 10.1261/rna.2922311
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-electron microscopy structure of the 30S subunit in complex with the YjeQ biogenesis factor

Abstract: YjeQ is a protein broadly conserved in bacteria containing an N-terminal oligonucleotide/oligosaccharide fold (OB-fold) domain, a central GTPase domain, and a C-terminal zinc-finger domain. YjeQ binds tightly and stoichiometrically to the 30S subunit, which stimulates its GTPase activity by 160-fold. Despite growing evidence for the involvement of the YjeQ protein in bacterial 30S subunit assembly, the specific function and mechanism of this protein remain unclear. Here, we report the costructure of YjeQ with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 57 publications
6
35
3
Order By: Relevance
“…Filtration assays (Supplemental Fig. S3; left panel) performed with buffers containing a concentration of NH 4 Cl ranging from 60 to 600 mM showed that at 300 mM NH 4 Cl, YjeQ bound to the 30S subunit at ∼1:1 ratio, which is the stoichiometry that has been previously established for the 30S+YjeQ complex (Daigle and Brown 2004;Himeno et al 2004;Guo et al 2011;Jomaa et al 2011b). …”
Section: Yjeq Requires the Carboxy-terminal Zinc-finger Domain To Binsupporting
confidence: 69%
See 1 more Smart Citation
“…Filtration assays (Supplemental Fig. S3; left panel) performed with buffers containing a concentration of NH 4 Cl ranging from 60 to 600 mM showed that at 300 mM NH 4 Cl, YjeQ bound to the 30S subunit at ∼1:1 ratio, which is the stoichiometry that has been previously established for the 30S+YjeQ complex (Daigle and Brown 2004;Himeno et al 2004;Guo et al 2011;Jomaa et al 2011b). …”
Section: Yjeq Requires the Carboxy-terminal Zinc-finger Domain To Binsupporting
confidence: 69%
“…Their roles in the maturation of the functional core of the 30S subunit may entail facilitating proper 17S rRNA folding, assisting processing of the rRNA, or mediating protein-RNA interactions. Cryo-electron microscopy (cryo-EM) (Sharma et al 2005;Datta et al 2007;Guo et al 2011;Jomaa et al 2011b) revealed that at least three factors, Era, YjeQ, and RbfA bind at or in close proximity to the decoding center at sites that are not overlapping, indicating that simultaneous binding is stereochemically possible. Consistently, genetic experiments (Bylund et al 1998(Bylund et al , 2001Inoue et al 2003Inoue et al , 2006Campbell and Brown 2008) suggested that these factors operate in conjunction rather than independently.…”
Section: Introductionmentioning
confidence: 99%
“…To globally assay changes in preribosomal protein constituents upon depletion of L7 or L8, we used iTRAQ, a semiquantitative mass spectrometric method ( Fig. 4; Ross et al 2004;Merl et al 2010;Jomaa et al 2011). In the case of depletion of L8, the iTRAQ data were confirmed using another tagged assembly factor, Noc2, to purify preribosomes (Supplemental Fig.…”
Section: L7 and L8 Assemble Early Into 90s Preribosomes Containing 35mentioning
confidence: 99%
“…This argues that RbfA has to act before KsgA in the cascade of biogenesis factors interacting with the pre-30S subunit. Furthermore, a recent structure of RsgA, which is the release factor of RbfA, on the 30S subunit shows RsgA in a conformation that would sterically exclude KsgA (54,55). This suggests that RsgA removes RbfA before KsgA can bind to the immature 30S subunit.…”
Section: Inactive Conformation Of 30s Mimics Ribosome Biogenesismentioning
confidence: 99%